Obesity-related hypertension: possible pathophysiological mechanisms - Vaněčková, Ivana; Maletínská, Lenka; Behuliak, Michal; Nagelová, Veronika; Zicha, Josef; Kuneš, Jaroslav (The Journal of endocrinology, 2014)
Hypertension is one of the major risk factors of cardiovascular diseases, but despite a century of clinical and basic research, the discrete etiology of this disease is still not fully understood. The same is true for obesity, which is recognized as a major global epidemic health problem nowadays. Obesity is associated with an increasing prevalence of the metabolic syndrome, a cluster of risk factors including hypertension, abdominal obesity, dyslipidemia, and hyperglycemia. Epidemiological studies have shown that excess weight gain predicts future development of hypertension, and the relationship between BMI and blood pressure (BP) appears to be almost linear in different populations. There is no doubt that obesity-related hypertension is a multifactorial and polygenic trait, and multiple potential pathogenetic mechanisms probably contribute to the development of higher BP in obese humans. These include hyperinsulinemia, activation of the renin-angiotensin-aldosterone system, sympathetic nervous system stimulation, abnormal levels of certain adipokines such as leptin, or cytokines acting at the vascular endothelial level. Moreover, some genetic and epigenetic mechanisms are also in play. Although the full manifestation of both hypertension and obesity occurs predominantly in adulthood, their roots can be traced back to early ontogeny. The detailed knowledge of alterations occurring in the organism of experimental animals during particular critical periods (developmental windows) could help to solve this phenomenon in humans and might facilitate the age-specific prevention of human obesity-related hypertension. In addition, better understanding of particular pathophysiological mechanisms might be useful in so-called personalized medicine.
Keywords: sympathetic nervous system; obezita; Multifactorial Inheritance; Humans; Hypertension; rat; Models, Biological; sympatický nervový systém; lidé; zvířata; hypertension; hmotnostní přírůstek; metabolický syndrom; epigenetics; krevní tlak; hypertenze; Metabolic Syndrome; biologické modely; critical developmental periods; Weight Gain; multifaktoriální dědičnost; Obesity; Animals; Sympathetic Nervous System; Blood Pressure; obesity; renin–angiotensin system